HUBUNGAN PENGETAHUAN TERHADAP SIKAP REMAJA DALAM MENANGGULANGI PREMENSTRUASI SYNDROME DI PRODI D-III KEBIDANAN STIKES PMC TAHUN 2017 - Nia Desriva; Melisa syafrina (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Premenstrual syndrome (PMS) is a collection of symptoms that usually from one weekbefore menstruation, and disappear when menstruation comes, although it may continueuntil menstruation stops. Based on a preliminary survey conducted found that studentswho know about premenstrual syndrome, namely 40%, and who do not know aboutpremenstrual syndrome that is 60% that did in the D3rd Prodi Midwifery STIKes PMC.Attitudes to reduce and mitigate the occurrence of premenstrual syndrome is needed. Toreduce the incidence of premenstrual syndrome, each individual must be able to cope withhow to manage your diet. If breast pain and headaches can rest and exercise. Thisresearch uses analytic design with cross sectional approach that aims to determine theattitude of youth in overcoming premenstrual syndrome. The research was carried out onstudents Prodi D3rd Midwifery STIKes Pekanbaru Medical Center totaling 113respondents through questionnaires. This research method using a proportional stratifiedrandom sampling. From the results of this study concluded that as many as 85% ofstudents knowledge about premenstrual syndrome included in the category of less, and asmuch as 53.1% of students in tackling attitudes premenstrual syndrome include enoughcategories. Relationship of knowledge to the youth attitude in tackling significantpremenstrual syndrome (ρ> 0.05), Results of this study can be recommended for furtherresearch, are expected to be able to search for other factors related about premenstrualsyndrome.Keywords: Knowledge, Attitudes, Adolescent, premenstrual syndrome